Atividade antipsoriática de extratos de tropaeolum majus (tropaeolaceae) padronizados em antocianinas sobre lesões Psoriasiformes induzidas em camundongos com imiquimode - Ferreira, Juliana Barreto dos Santos Silva (2017)
Introduction: Two components served as the basis for the development of this study. On the one hand, a disease whose treatment is palliative, limited in efficacy and related to adverse effects; psoriasis. On the other hand, a plant with a history in popular medicine (Tropaeolum majus, known mainly as capuchinha) for which there was a body of literature that allowed to hypothesize that any product derived from it could have a therapeutic effect on psoriatic lesions. Objective: To evaluate the antipsoriatic potential of Tropaeolum majus extracts on psoriasis-like wounds induced in mice with imiquimod. Methods: The ethyl acetate, ethanolic and hydroethanolic extracts were obtained from the plant’s flowers by exhaustive maceration. Concentration of anthocyanins in the extracts was determined by the differential pH method. Balb-c mice (n = 12) groups were formed: normal and negative control groups treated with water and 10% glycerol, positive control treated with 0.05 mg/mL clobetasol and groups receiving extract (50 mg/mL). Wounds were induced on the back of mice. The treatments were daily for five days. Two hours after the administration of the last doses, half of each group was euthanized serving to collect cutaneous tissue for analyzes of concentration of TNF-α, IL-1β, ERK phosphorylation, lipid peroxidation, protein carbonylation and reduced glutathione (GSH). The other half of animals were kept alive and served to determine the time required for wounds’ clearance. Results: The concentration of anthocyanins was 0.62 ± 0.09; 6.96 ± 0.90 and 10.86 ± 0.64 mg/g in the ethyl acetate, ethanolic and hydroethanolic extracts, respectively. The severity of wounds was reduced by 35% and up to 45% in mice treated with ethanolic and hydroethanolic extract, as well as time for wounds’ clearance (~ twice and > 3 times), respectively. The production of TNF-α and IL-1β was normalized by ethanolic and hydroethanolic extracts, as well as lipid peroxidation and protein carbonylation. Only these extracts recovered GSH levels, being the most potent activity caused by the hydroethanolic extract. Conclusion: Data suggested a relationship between antipsoriatic activity and anthocyanins. The most potent antipsoriatic activity was caused by the hydroethanolic extract, which had the highest concentration of anthocyanins among the extracts evaluated.